Ecoeducare: Implementasi Program Bank Sampah sebagai Media Pendidikan Kewirausahaan Untuk Santri - Najib, Ahmad Ainun; Alfian, Zaki Gufron; M. Toufikur Rozikin (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2024)
Abstract Pesantren (Islamic boarding schools) as traditional educational institutions have undergone a transformation in their role of providing entrepreneurial education to their students. However, many pesantren still view entrepreneurship education as less important compared to religious education. This study focuses on the implementation of Santri (student) Entrepreneurship Education through a Waste Bank at Pondok Pesantren Darussalam Blokagung Banyuwangi. The research employs a qualitative descriptive approach. The findings of this study show that the implementation of Santri entrepreneurship education through the Waste Bank at Pondok Pesantren Darussalam Blokagung Banyuwangi is a non-formal education based on community empowerment. The approach used in implementing the program is experiential learning, which emphasizes environmental awareness and creativity to foster an entrepreneurial mindset. Additionally, the implementation also incorporates leadership management and financial management theories. This research also observes positive changes in the Santri, encompassing five aspects: capability, self-confidence, connections, character, and care. Keywords: Education, Entrepreneurship, Santri.